Dreams of joy [compact disc, unabridged] : a novel - See, Lisa (Random House, Inc., 2011)
In 1957, family secrets prompt Joy to travel to Shanghai and search for the father she never knew. Entranced with idealism and her father's wisdom, she joins the New Society movement that has swept across China.